PERANCANGAN APLIKASI RAPOR ONLINE DENGAN FRAMEWORK CODEIGNITER BERBASIS WEB PADA SD ISLAM AL FALAH - Angga Bondan Bachtiar; Resti Amalia (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The report card is a report on student learning outcomes in the form of a book containing the value of learning achievement while at school. The aim is to simplify the process of inputting and processing student grades and all educational unit activities can be used comprehensively, so that education in elementary schools is well planned using this web-based online report card application design database, so that it can be directly accessed and value information can be conveyed properly. In addition, the system interface is implemented in accordance with the existing report card display so that the system can be used efficiently and effectively so as to produce accurate value calculations. The development method used in designing this web-based online report card application is the spiral method. The spiral method is used because the development steps in this spiral method are more suitable for use in designing web-based online report cards applications. Based on the results obtained in the design of this application, the following suggestions can be given. For principals, homerooms, teachers, students, and parents, it is hoped that this web-based online report card application can be considered as an alternative application that can be used to simplify the process of making or working on report cards. users can more easily use it and feel more comfortable